1997
DOI: 10.1016/s0003-9993(97)90076-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease risk indicators, aerobic power, and physical activity in men with spinal cord injuries

Abstract: ABSTRACT.Janssen TWJ, van Oers CAJM, van Kamp GJ, TenVoorde BJ, van der Woude LHV, Hollander AP. Coronary heart disease risk indicators, aerobic power, and physical activity in men with spinal cord injuries. Arch Phys Med Rehabil 1997;78:697-705. Objective: To compare the lipid and (apo-)lipoprotein profile and blood pressure of men with long-standing spinal cord injuries (SCI) to those of an age-matched able-bodied (AB) population, and to assess the most important determinants of this profile and blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 34 publications
1
49
1
3
Order By: Relevance
“…Expressed as weight (kg) divided by height (m 2 ), BMI allows classification of able-bodied adults as underweight, normal weight, overweight or obese, using the World Health Organization criteria in Table 2. 12 Mean BMI values in studies of persons with long-standing SCI range from 20 to 27, 5,6,10,[13][14][15][16][17][18] consistent with the classifications of normal and overweight, but inconsistent with classification based on measured percent fat mass. [4][5][6][7][8][9][10][11] One reason for the underestimation of obesity using BMI may be the potential measurement error associated with determination of weight and/or height in persons with SCI.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 92%
See 3 more Smart Citations
“…Expressed as weight (kg) divided by height (m 2 ), BMI allows classification of able-bodied adults as underweight, normal weight, overweight or obese, using the World Health Organization criteria in Table 2. 12 Mean BMI values in studies of persons with long-standing SCI range from 20 to 27, 5,6,10,[13][14][15][16][17][18] consistent with the classifications of normal and overweight, but inconsistent with classification based on measured percent fat mass. [4][5][6][7][8][9][10][11] One reason for the underestimation of obesity using BMI may be the potential measurement error associated with determination of weight and/or height in persons with SCI.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 92%
“…20 Despite this, recalled height has been used in a number of studies reporting BMI in subjects with chronic SCI. 5,16,17 An alternative is to measure length. Jones et al 21 reported the Pearson's correlation coefficient for height (measured by wall-mounted stadiometer) versus length (by the electronic ruler function of DXA) to be 0.996 (P ¼ 0.0001).…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 99%
See 2 more Smart Citations
“…6 However, behavioral factors can also be associated with unfavorable changes in body mass and lipid profile. Previous studies found an effect of smoking, 7 alcohol consumption, body mass, active lifestyle 7 and fitness 8 on lipid profiles in individuals with SCI. The effect of these lifestyle factors on body mass seems less clear 7 or has not yet been investigated.…”
Section: Introductionmentioning
confidence: 95%